Pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes and preparation method of pioglitazone hydrochloride microneedle drug delivery system

Through pioglitazone hydrogel microneedle delivery system and iontophoresis technology, the problem that pioglitazone hydrochloride is difficult to penetrate the skin is solved, and efficient and stable blood drug concentration is achieved, improving the effect of diabetes treatment and the convenience of patients' medication use is achieved. .

CN119455243APending Publication Date: 2025-02-18ZHEJIANG MEDICAL COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411660199.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively penetrate the skin through traditional methods of penetration, so as to achieve the blood drug concentration required for the treatment of type II diabetes.

Method used

The pioglitazone hydrogel microneedle delivery system is adopted to combine electrolytic gel patches and smart wearable devices to achieve transdermal absorption of pioglitazone hydrochloride using iontophoresis technology.

Benefits of technology

It improves the transdermal administration efficiency of pioglitazone hydrochloride, reduces gastrointestinal side effects, maintains a more stable blood drug concentration, and improves the patient's medication compliance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455243A_ABST
    Figure CN119455243A_ABST
Patent Text Reader

Abstract

The invention discloses a pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes and a preparation method of the pioglitazone hydrochloride microneedle drug delivery system. The pioglitazone hydrochloride microneedle drug delivery system comprises a pioglitazone hydrochloride hydrogel microneedle patch, an electric moistening gel patch and intelligent wearable equipment, the pioglitazone hydrochloride hydrogel microneedle comprises the following components in percentage by mass: 0.5%-2.0% of pioglitazone hydrochloride, 12%-17% of a pioglitazone hydrochloride microneedle skeleton, 1%-2% of an auxiliary skeleton material, 0%-0.5% of a conductive material, 10%-20% of a glucose response material, 0.5%-1% of a fluorescent material and 57.5%-76% of ultrapure water, the electrowetting gel patch is divided into an inner layer and an outer layer, the inner layer is prepared from, by weight, 2.0%-5.0% of a gel framework material, 0%-0.5% of a conductive material and 94.5%-98% of ultrapure water, and the outer layer is prepared from, by weight, 3%-12% of a matrix, 0.1%-0.5% of a cross-linking agent, 20%-60% of a humectant, 1%-5% of a tackifier, 2%-6% of an excipient, 0.2%-0.8% of a cross-linking regulator, 0.02%-0.08% of a complexing agent and 22%-58% of water. The intelligent wearable device is used for monitoring the blood glucose of the human body, when the blood glucose level exceeds a preset threshold value, drug release is accurately controlled through the drug delivery module, and the treatment efficiency and safety are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical technology, specifically to a pioglitazone hydrochloride microneedle delivery system for the treatment of type II diabetes and its preparation method. Background Technology

[0002] Diabetes mellitus is a metabolic disorder of carbohydrates, proteins, and fats caused by insufficient insulin secretion and impaired insulin utilization, primarily characterized by hyperglycemia. Based on its pathogenesis, it can be classified into insulin-dependent diabetes mellitus (Type 1), non-insulin-dependent diabetes mellitus (Type 2), gestational diabetes mellitus, secondary diabetes mellitus, and malnutrition-related diabetes mellitus. Type 2 diabetes mellitus, as a chronic metabolic disease, accounts for more than 90% of all diabetes cases, with a peak incidence between 35 and 40 years of age. The main characteristic of this type of diabetes is persistent hyperglycemia, which easily leads to many long-term complications in the later stages of the disease, posing a significant threat to public health in modern society.

[0003] Pioglitazone hydrochloride (PIO) belongs to the thiazolidinedione class of antidiabetic drugs and has a good hypoglycemic effect in the clinical use of type 2 diabetes. This drug regulates glucose and lipid metabolism by stimulating peroxisome proliferation-activating receptor-γ (PPAR-γ), effectively reducing insulin resistance. Currently, pioglitazone hydrochloride is available in oral formulations such as tablets, capsules, and dispersible tablets. Oral administration can cause adverse reactions such as gastrointestinal discomfort, vomiting, and nausea, reducing patient compliance. Exploring diverse routes of administration, such as transdermal administration, may provide more options to meet the needs of a wider range of patients.

[0004] Transdermal drug delivery systems (TDDS) are a route of drug administration that delivers medication through the skin to achieve systemic or local therapeutic effects. Compared to traditional oral administration, TDDS bypasses the first-pass effect of the liver and intestines, delivering drugs directly into the body through the skin. This not only reduces gastrointestinal side effects but also maintains more stable blood drug concentrations, avoiding drastic fluctuations in drug concentration and reducing toxic side effects, while also improving patient adherence. However, the molecular size and hydrophilic nature of pioglitazone hydrochloride make it difficult to efficiently penetrate the skin barrier using traditional permeation-enhancing methods to achieve the required therapeutic blood concentrations. Summary of the Invention

[0005] To address the problems existing in the prior art, the present invention provides a pioglitazone hydrochloride microneedle delivery system for the treatment of type II diabetes and its preparation method.

[0006] In a first aspect, embodiments of the present invention provide a pioglitazone hydrochloride microneedle delivery system for the treatment of type II diabetes, the system comprising:

[0007] The pioglitazone hydrogel microneedle patch comprises, by weight: 0.5%-2.0% pioglitazone hydrochloride, 12%-17% microneedle matrix material, 1%-2% microneedle auxiliary matrix material, 0%-0.5% conductive material, 10%-20% glucose-responsive material, 0.5%-1% fluorescent material, and 57.5%-76% ultrapure water;

[0008] An electrolubricating gel patch, comprising an inner layer and an outer layer; the inner layer, by weight, comprises: 2.0-5.0% gel matrix material, 0%-0.5% conductive material, and 94.5%-98% ultrapure water; the outer layer, by weight, comprises: 3-12% matrix matrix material, 0.1-0.5% crosslinking agent, 20-60% humectant, 1-5% tackifier, 2-6% excipient, 0.2-0.8% crosslinking regulator, 0.02-0.08% complexing agent, and 15.62-73.68% ultrapure water;

[0009] A smart wearable device includes a blood glucose detection module and a drug delivery module. The blood glucose detection module uses fluorescent materials in a pioglitazone hydrogel microneedle patch to monitor changes in blood glucose concentration in the interstitial fluid of the skin in real time via FRET technology. When the detected blood glucose concentration exceeds a preset threshold, the blood glucose detection module transmits an iontophoresis activation signal to the drug delivery module. Upon receiving the iontophoresis signal from the blood glucose detection module, the drug delivery module wets the pioglitazone hydrogel microneedle patch with an electro-lubricating gel patch, achieving transdermal absorption of pioglitazone hydrochloride with the assistance of iontophoresis.

[0010] Secondly, embodiments of the present invention provide a method for preparing a pioglitazone hydrochloride microneedle delivery system for the treatment of type II diabetes, wherein the preparation process of the pioglitazone hydrochloride hydrogel microneedle patch includes:

[0011] Preparation of blank microneedle solution: Prepare a blank microneedle solution by weight percentage, specifically including 12%-17% microneedle framework material, 1%-2% auxiliary framework material, 10%-20% glucose-responsive material, 0.5%-1% fluorescent material, and 57.5%-76% ultrapure water; stir all the above components thoroughly until completely dissolved, then add 0%-0.5% conductive material to the mixed solution, and continue stirring until the conductive material is completely dissolved to obtain the blank microneedle solution;

[0012] Preparation of drug-containing microneedle solution: Add 0.5%-2.0% pioglitazone hydrochloride to the blank microneedle solution to form a homogeneous drug-containing microneedle solution;

[0013] Mold filling: Add the drug-containing microneedle solution into the microneedle mold, and use a vacuum method to ensure that the drug-containing microneedle solution fully enters the mold needle holes until the mold is filled;

[0014] Drying and demolding: The mold containing the microneedle solution was left to stand at room temperature and dried. After demolding, pioglitazone hydrogel microneedle patch was obtained.

[0015] The preparation process of the electrolubricating gel patch includes:

[0016] Preparation of inner electrolubricating gel patch: Weigh 2.0-5.0% gel skeleton material and 94.5%-98% ultrapure water according to the weight ratio, stir thoroughly to dissolve completely, then add 0%-0.5% conductive material to the mixed solution, coat it on the first release film, dry it, and then combine it with the second release film, and cut it into inner electrolubricating gel patch of the target size;

[0017] Preparation of the outer electrolubricating gel patch: Weigh 20-60% humectant, 3-12% matrix skeleton material, 0.1-0.5% crosslinking agent, and 0.02-0.08% complexing agent according to the weight ratio, and mix them evenly under stirring to obtain a glycerol phase; Take 15.62-73.68% purified water, add 1-5% thickener, 2-6% excipient, and 0.2-0.8% crosslinking regulator, and dissolve them completely to obtain an aqueous phase; Add the aqueous phase to the glycerol phase under stirring until it is mixed evenly to form a gel morphology, degas to obtain the gel body, coat the gel onto the first release film, dry it, and then laminate it with the second release film; Then cut it in two steps. First, cut a patch with a diameter slightly larger than the inner electrolubricating gel patch to cover the area of ​​the pioglitazone hydrogel microneedle patch. Second, cut off a patch with the same area as the inner electrolubricating gel from the cut patch to obtain an outer electrolubricating gel patch with a hollow center;

[0018] Composite inner electrolubricating gel patch and outer electrolubricating gel patch: The inner electrolubricating gel patch is placed inside the hollow outer electrolubricating gel patch. The release forces of the inner and outer anti-adhesive films are the same on the same side. Then, the second release anti-adhesive films of the inner and outer electrolubricating gels are peeled off, and a new second release anti-adhesive film is re-laminated to obtain the electrolubricating gel patch.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] This invention provides a pioglitazone hydrochloride microneedle drug delivery system for the treatment of type II diabetes. In this invention, the proportion of the microneedle matrix material in the pioglitazone hydrogel microneedles is 12%-17%. While meeting the drug loading requirements for treatment, the viscosity of the microneedle solution is controlled, thereby ensuring the preparation and application effects of the microneedles. This invention selects poly(vinyl methyl ether-alt-maleic anhydride) as the microneedle matrix material, which improves the solubility of the poorly soluble drug pioglitazone hydrochloride in water, effectively solving the problem of poor water solubility of pioglitazone hydrochloride and its inability to achieve drug loading. Furthermore, poly(vinyl methyl ether-alt-maleic anhydride) rapidly absorbs water and swells upon contact with water to form a hydrogel, rapidly releasing the drug.

[0021] In this invention, the auxiliary matrix material in the pioglitazone hydrogel microneedles accounts for 1%-2% to balance the toughness and hardness of the microneedles. The amount of conductive sodium chloride added is controlled within the range of 0%-0.5% to ensure effective transdermal drug delivery under electroosmosis, while avoiding a competitive effect that would reduce the drug permeation rate due to excessive amounts. The proportion of the active drug, pioglitazone hydrochloride, is controlled at 0.5%-2% to meet the required drug amount for treatment, while preventing precipitation problems caused by excessively high drug concentrations. Attached Figure Description

[0022] Figure 1 Figure 1 shows the textural results of microneedle tip hardness and overall toughness tests for pioglitazone hydrochloride examples;

[0023] Figure 2 Images of pioglitazone hydrochloride microneedles under different conditions (a. morphology observed with the naked eye; b. microneedle morphology under a bright field (16x) optical microscope; c. microneedle structure under a scanning electron microscope).

[0024] Figure 3 Diagram showing the microneedle puncture performance of pioglitazone hydrochloride;

[0025] Figure 4 Figures showing the in vitro and in vivo swelling properties of pioglitazone hydrochloride microneedles (a. in vitro; b. in vivo);

[0026] Figure 5 Cumulative skin permeation curve of the effect of electrowetting gel layer on drug permeation in vitro;

[0027] Figure 6 This is a diagram of an ex vivo skin permeation experiment.

[0028] Figure 7 The graphs show the cumulative permeation curves of ex vivo skin in Example 3, Comparative Examples 3-1 and 3-2.

[0029] Figure 8 The cumulative permeation curves of ex vivo skin in Example 3 and Comparative Examples 3-3 and 3-4 are shown.

[0030] Figure 9 This is a cumulative permeation curve of ex vivo skin under different current conditions in Example 3;

[0031] Figure 10 This is a cumulative skin permeation curve of ex vivo skin after 48 hours in Example 3;

[0032] Figure 11 The cumulative permeation curves of ex vivo skin in Example 4, Comparative Examples 3-3 and 3-4 are shown.

[0033] Figure 12 Example 4 serves as a control; it shows the cumulative skin penetration curve when the microneedle backing does not contain any drug.

[0034] Figure 13 In vivo imaging of rat skin penetration (a. ROI 1 ionization group 3 min, ROI 2 control group 3 min; b. ROI 1 ionization group 30 min, ROI 2 control group 30 min);

[0035] Figure 14 The changes in blood glucose levels over 8 consecutive days in type II diabetic rats (a. blood glucose Δ values ​​for each group; b. oral administration group; c. ionized microneedle group; d. model group);

[0036] Figure 15 Image showing skin irritation of pioglitazone hydrochloride microneedles;

[0037] Figure 16 Sections of tissue with skin irritation;

[0038] Figure 17 Design electronic schematics for wearable devices. Detailed Implementation

[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] It should be noted that, unless otherwise specified, the features in the following embodiments and implementation methods can be combined with each other.

[0041] In a first aspect, embodiments of the present invention provide a pioglitazone hydrochloride microneedle delivery system for the treatment of type II diabetes, the system comprising: a pioglitazone hydrochloride hydrogel microneedle patch;

[0042] The pioglitazone hydrogel microneedle patch comprises, by weight: 0.5%-2.0% pioglitazone hydrochloride, 12%-17% microneedle matrix material, 1%-2% microneedle auxiliary matrix material, 0%-0.5% conductive material, 10%-20% glucose-responsive material, 0.5%-1% fluorescent material, and 57.5%-76% ultrapure water.

[0043] Furthermore, the microneedle framework material is poly(vinyl methyl ether-alt-maleic anhydride); the microneedle auxiliary framework material is one of polyvinyl alcohol 124 and polyvinyl alcohol 350; the conductive material is sodium chloride; the glucose-responsive material is chitosan-phenylboronic acid derivative (CS-APB); the fluorescent material uses one of Alexa Fluor 488 and Alexa Fluor 568 as the fluorescent donor and Rhodamine B as the fluorescent acceptor, and the fluorescent donor and fluorescent acceptor are mixed in a molar ratio of 2:1.

[0044] It should be noted that in pioglitazone hydrogel microneedles, the proportion of microneedle matrix material is 12%-17%. If it is less than 12%, the drug loading of the microneedles cannot meet the treatment needs, while if it is more than 17%, it will lead to an increase in the viscosity of the microneedle solution, which will affect the preparation and application effect of the microneedles.

[0045] The auxiliary framework material in microneedles accounts for 1%-2% of the total material, aiming to balance the toughness and hardness of the microneedles. Below 1%, the needle tip toughness is insufficient, making the needle prone to breakage during drug delivery. Above 2%, the needle tip hardness is too low, making it difficult for the needle to penetrate the stratum corneum during drug delivery.

[0046] The amount of conductive sodium chloride added is controlled within the range of 0%-0.5% to ensure effective transdermal drug penetration under electroosmosis, while avoiding a competitive effect that would reduce the drug penetration rate due to excessive amounts. The proportion of the active drug pioglitazone hydrochloride is controlled at 0.5%-2% to meet the required amount of drug for treatment, while preventing precipitation problems caused by excessively high drug concentrations.

[0047] In this example, poly(vinyl methyl ether-alt-maleic anhydride) was selected as the microneedle matrix material. This material has high mechanical strength, good swelling and conductivity in water, and the addition of conductive materials further adjusts the conductivity. When used in conjunction with an iontophoresis system, the transdermal drug penetration is significantly increased. After being fabricated into microneedles, the needle tip can directly penetrate the stratum corneum of the skin and rapidly absorb water and swell intradermally to form a stable drug delivery channel. When combined with an iontophoresis device, the drug can be efficiently delivered through the skin under the drive of an electric current.

[0048] To address the issue of insufficient drug loading in traditional soluble microneedles, this invention also loads drugs onto the backing of the microneedles. The drugs on the backing can also penetrate the skin and enter the body through the gel microneedle channels under iontophoresis conditions, thus solving the problem of insufficient drug loading at the microneedle tip.

[0049] Furthermore, the system also includes:

[0050] An electrolubricating gel patch, comprising an inner layer and an outer layer; the inner layer, by weight, comprises: 2.0-5.0% gel matrix material, 0%-0.5% conductive material, and 94.5%-98% ultrapure water; the outer layer, by weight, comprises: 3-12% matrix matrix material, 0.1-0.5% crosslinking agent, 20-60% humectant, 1-5% tackifier, 2-6% excipient, 0.2-0.8% crosslinking regulator, 0.02-0.08% complexing agent, and 15.62-73.68% ultrapure water;

[0051] Smart wearable devices, including blood glucose detection modules and drug delivery modules;

[0052] The blood glucose detection module is used to monitor changes in blood glucose concentration in the interstitial fluid of the skin in real time using fluorescent materials in the pioglitazone hydrogel microneedle patch and FRET technology. When the blood glucose concentration is detected to be higher than a preset threshold, the blood glucose detection module transmits an iontophoresis activation signal to the drug delivery module.

[0053] The drug delivery module is used to receive the iontophoresis signal from the blood glucose detection module and then wet the pioglitazone hydrogel microneedle patch with an electro-lubricating gel patch to achieve transdermal absorption of pioglitazone hydrochloride with the assistance of iontophoresis.

[0054] It should be noted that this invention improves the solubility of the poorly soluble drug pioglitazone hydrochloride in water by using poly(vinyl methyl ether-alt-maleic anhydride) as the water-soluble backbone material. This effectively solves the problem of poor water solubility of pioglitazone hydrochloride, which hinders drug loading. Furthermore, poly(vinyl methyl ether-alt-maleic anhydride) rapidly absorbs water and swells to form a hydrogel, accelerating drug release and penetration within the skin. The inner gel layer of the electrolubricating gel patch provides a water source, addressing the issue of low skin moisture and long expansion time for microneedles without external water. The outer gel layer provides skin-friendly adhesion, bonding the skin to the smart wearable device to form a complete pioglitazone hydrochloride smart drug delivery system. This invention utilizes a hydrogel microneedle design to effectively overcome the limitations of large molecular chemical drugs penetrating the skin, improving transdermal drug delivery efficiency and dosage. It avoids the pain and inconvenience of injection and mitigates gastrointestinal side effects that may occur with oral administration, greatly enhancing patient convenience and comfort.

[0055] Further, the gel skeleton material is hydroxypropyl methylcellulose; the matrix skeleton material is partially neutralized sodium polyacrylate; the crosslinking agent is one or more of aluminum chloride, aluminum hydroxide, and aluminum hydroxyacetate mixed in any proportion; the humectant is glycerin or propylene glycol; the thickener is one or more of povidone, hydroxypropyl methylcellulose, carbomer, and sodium carboxymethyl cellulose mixed in any proportion; the excipient is gelatin or polyvinyl alcohol; the crosslinking regulator is tartaric acid or citric acid; and the complexing agent is disodium ethylenediaminetetraacetate or sodium calcium ethylenediamineacetate.

[0056] Furthermore, a first release anti-adhesive film and a second release anti-adhesive film are respectively provided on both sides of the electro-lubricating gel layer patch; the release force of the first release anti-adhesive film is greater than that of the second release anti-adhesive film; in use, after the first release anti-adhesive film is peeled off, the electro-lubricating gel layer patch can be connected to the smart wearable device, and after the second release anti-adhesive film is peeled off, the electro-lubricating gel layer patch can be connected to the pioglitazone hydrogel microneedle patch.

[0057] Furthermore, the administration process of the pioglitazone hydrochloride microneedle delivery system includes:

[0058] The blood glucose threshold is set as follows: blood glucose level continuously exceeds 10.0 mmol / L within 3 hours or blood glucose level continuously remains between 7.2 and 10 mmol / L within 8 hours.

[0059] Remove the protective layer of the pioglitazone hydrochloride microneedle patch, allowing the pioglitazone hydrochloride microneedle tip to pierce the skin. Then, apply the electrolubricating gel patch with the second release film removed to the outside of the pioglitazone hydrochloride microneedle patch, and then remove the first release film of the electrolubricating gel patch.

[0060] The smart wearable device is worn over the electrolubricating gel patch. The blood glucose detection module of the smart wearable device uses the fluorescent material in the pioglitazone hydrogel microneedle patch to monitor the changes in blood glucose concentration in the interstitial fluid of the skin in real time through FRET technology. When the detected blood glucose concentration is higher than the preset threshold, the blood glucose detection module sends an iontophoresis signal to the drug delivery module. Once iontophoresis is initiated, the drug delivery module adjusts the current to achieve precise release of pioglitazone hydrochloride.

[0061] Furthermore, the smart wearable device also includes an LCD display module, which is used to display the current blood glucose level and drug administration status in real time; the drug administration module, based on the iontophoresis signal sent by the blood glucose detection module, allows the drug pioglitazone hydrochloride in the microneedle patch to penetrate the skin and enter the body under iontophoresis to regulate the patient's blood glucose level.

[0062] It should be noted that the FRET sensor built into the smart wearable device provided by this invention can monitor blood glucose levels in the interstitial fluid of the skin in real time. The FRET sensor detects the energy transfer efficiency between the fluorescent donor and acceptor, E = 1 / (1+(R / R0)). 6 This accurately reflects changes in blood glucose concentration, as shown in the following formula:

[0063]

[0064] Where R is the FRET ratio, which is monitored by fluorescence I. A / I D R max R0 is the FRET ratio at saturated glucose concentration; R0 is the baseline FRET value without glucose; [Gluc] is the glucose concentration, and Kd is the dissociation constant.

[0065] The fluorescence signal is ultimately converted into an electrical signal and transmitted to the microprocessor. The microprocessor analyzes blood glucose data in real time based on a preset blood glucose threshold (i.e., a blood glucose level consistently exceeding 10.0 mmol / L within 3 hours or consistently between 7.2 and 10 mmol / L within 8 hours). When the blood glucose level exceeds the set threshold, the drug delivery module is activated. Upon receiving the control signal, the drug delivery module adjusts the current, providing the necessary electrical energy to the pioglitazone hydrochloride hydrogel microneedle patch through the electrolubricating gel patch, initiating the iontophoresis process and rapidly promoting the transdermal absorption of pioglitazone hydrochloride. When blood glucose returns to the normal range, the system automatically disconnects the iontophoresis and pauses the transdermal drug delivery. This on-demand, precise drug delivery method ensures timely blood glucose control, prevents potential risks associated with hyperglycemia, and avoids unnecessary drug absorption.

[0066] Meanwhile, the smart device's LCD display module shows the current blood glucose level and drug administration status in real time, allowing users to intuitively understand the device's operation. When the blood glucose level returns to the normal range, and the blood glucose detection module detects that the blood glucose value has dropped below the preset threshold again, the microcontroller will automatically generate a control signal to stop iontophoresis, disconnect the current supply, and pause drug administration. This control mechanism ensures that the drug is administered on demand and avoids drug overdose by precisely regulating the drug release process.

[0067] Through the aforementioned control mechanism, the smart wearable device achieves precise and coordinated control of the transdermal absorption of pioglitazone hydrogel microneedle patches. This automated control method not only improves the targeting and efficiency of treatment but also enables precise management and control of the patient's condition, reducing the patient's reliance on continuous blood glucose monitoring and manual drug administration. Simultaneously, the preset blood glucose threshold is set based on clinical safety standards, ensuring that the drug administration procedure is only initiated when necessary, avoiding excessive intervention and guaranteeing timely and effective treatment for patients with abnormal blood glucose levels. This application employs a combination of two physical permeation-enhancing methods—microneedle technology and iontophoresis—to promote transdermal drug absorption. Furthermore, diabetes treatment is better suited to precise and personalized treatment based on the patient's blood glucose levels, and wearable treatment devices represent a future trend in pharmaceutical development.

[0068] Secondly, embodiments of the present invention provide a method for preparing a pioglitazone hydrochloride microneedle delivery system for the treatment of type II diabetes, wherein the preparation process of the pioglitazone hydrochloride hydrogel microneedle patch includes:

[0069] Preparation of blank microneedle solution: Prepare a blank microneedle solution by weight percentage, specifically including 12%-17% microneedle framework material, 1%-2% auxiliary framework material, 10%-20% glucose-responsive material, 0.5%-1% fluorescent material, and 57.5%-76% ultrapure water; stir all the above components at a stirring temperature of 90℃ and a stirring speed of 500r / min for at least 2 hours until completely dissolved, then add 0%-0.5% conductive material to the mixed solution and continue stirring until the conductive material is completely dissolved to obtain the blank microneedle solution;

[0070] Preparation of drug-containing microneedle solution: Add 0.5%-2.0% pioglitazone hydrochloride to the blank microneedle solution to form a homogeneous drug-containing microneedle solution;

[0071] Mold filling: Add the drug-containing microneedle solution into the microneedle mold, and use a vacuum method to ensure that the drug-containing microneedle solution fully enters the mold needle holes until the mold is filled;

[0072] Drying and demolding: The mold containing the microneedle solution is left to stand at room temperature and dried. After demolding, pioglitazone hydrochloride hydrogel microneedle patches are obtained, and then each microneedle patch is packaged with a protective layer.

[0073] Furthermore, the preparation process of the electrowetting gel patch includes:

[0074] Preparation of inner electrolubricating gel patch: Weigh 2.0-5.0% gel skeleton material and 94.5%-98% ultrapure water according to the weight ratio, stir thoroughly to dissolve completely, then add 0%-0.5% conductive material to the mixed solution, coat it on the first release film, dry it, and then combine it with the second release film, and cut it into inner electrolubricating gel patch of the target size;

[0075] Preparation of the outer electrolubricated gel patch: Weigh 20-60% humectant, 3-12% matrix skeleton material, 0.1-0.5% crosslinking agent, and 0.02-0.08% complexing agent according to the weight ratio, and mix them evenly under stirring to obtain the glycerol phase; Take 15.62-73.68% purified water, add 1-5% thickener, 2-6% excipient, and 0.2-0.8% crosslinking regulator, and dissolve them completely to obtain the aqueous phase; Add the aqueous phase to the glycerol phase under stirring until the mixture is evenly mixed to form a gel. The gel body was degassed and coated onto a first release liner. After drying, it was then laminated with a second release liner. The gel body was then cut in two stages. First, a patch with a diameter slightly larger than that of the inner electrolubricating gel patch was cut to cover the area of ​​the pioglitazone hydrogel microneedle patch (in this example, the first cut diameter was 4 cm larger than that of the inner electrolubricating gel patch). Second, a patch with the same area as the inner electrolubricating gel was removed from the cut patch to obtain an outer electrolubricating gel patch with a hollow center.

[0076] Composite inner electrolubricating gel patch and outer electrolubricating gel patch: The inner electrolubricating gel patch is placed inside the hollow outer electrolubricating gel patch. The release forces of the inner and outer anti-adhesive films are the same on the same side. Then, the second release anti-adhesive films of the inner and outer electrolubricating gels are peeled off, and a new second release anti-adhesive film is re-laminated to obtain the electrolubricating gel patch.

[0077] The following embodiments further illustrate the present invention, but the embodiments of the present invention are merely for illustrative purposes and not for limiting the present invention. Therefore, any simple modifications to the present invention based on the method of the present invention are within the scope of protection of the present invention.

[0078] Example 1

[0079] This invention provides a method for preparing a pioglitazone hydrogel microneedle solution. The total amount of the drug-containing microneedle solution is 500 mg, including 5.0 mg of pioglitazone hydrochloride, 8.0 mg of polyvinyl alcohol 350, 80.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 1.5 mg of sodium chloride, 75 mg of CS-APB, 5 mg of Alexa Fluor 488, and 325.5 mg of ultrapure water.

[0080] The specific process is as follows: Weigh 8.0 mg of polyvinyl alcohol 350 and add it to 325.5 mg of ultrapure water. Heat and stir to 90°C. After the polyvinyl alcohol 350 is completely dissolved, add 80.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 75 mg of CS-APB, and 5 mg of Alexa Fluor 488. Continue stirring at 90°C and 500 rpm for 2 hours. After cooling the stirred solution to room temperature, add 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride. Continue stirring at 25°C and 500 rpm for 2 hours to obtain the drug-containing microneedle solution.

[0081] Comparative Example 1-1

[0082] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring temperature of the mixed solution after the drug was added remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 35°C and 500 r / min for 2 hours to obtain the drug-containing microneedle solution.

[0083] Comparative Examples 1-2

[0084] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring temperature of the mixed solution after the drug was added remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 45°C and 500 r / min for 2 hours to obtain the drug-containing microneedle solution.

[0085] Comparative Examples 1-3

[0086] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring temperature of the mixed solution after the drug was added remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 55°C and 500 r / min for 2 hours to obtain the drug-containing microneedle solution.

[0087] Comparative Examples 1-4

[0088] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring rate of the mixed solution after the drug was added remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 25°C and 250 r / min for 2 hours to obtain the drug-containing microneedle solution.

[0089] Comparative Examples 1-5

[0090] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring rate of the mixed solution after the drug was added remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 750 r / min for 2 h at 25 °C to obtain the drug-containing microneedle solution.

[0091] Comparative Examples 1-6

[0092] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring rate of the mixed solution after the drug was added remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 1000 r / min for 2 h at 25 °C to obtain the drug-containing microneedle solution.

[0093] Comparative Examples 1-7

[0094] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring time of the mixed solution after adding the drug was changed, while the other preparation steps remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 25°C and 500 r / min for 1 h to obtain the drug-containing microneedle solution.

[0095] Comparative Examples 1-8

[0096] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring time of the mixed solution after adding the drug was changed, while the other preparation steps remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 25°C and 500 r / min for 3 hours to obtain the drug-containing microneedle solution.

[0097] Comparative Examples 1-9

[0098] The drug-containing microneedle solution was prepared in the same manner as in Example 1, except that the stirring time of the mixed solution after adding the drug was changed, while the other preparation steps remained the same. Specifically, after the mixed solution was cooled, 5.0 mg of pioglitazone hydrochloride and 1.5 mg of sodium chloride were added, and the mixture was stirred at 25°C and 500 r / min for 4 hours to obtain the drug-containing microneedle solution.

[0099] Example 2

[0100] This invention provides a method for preparing a pioglitazone hydrogel microneedle formulation, wherein the total amount of microneedles is 500 mg, including 2.5 mg of pioglitazone hydrochloride, 5.0 mg of polyvinyl alcohol 124, 60.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 50 mg of CS-APB, 2.5 mg of Alexa Fluor 488, and 380 mg of ultrapure water.

[0101] The specific process is as follows: Weigh 5.0 mg of polyvinyl alcohol 124 and add it to 380 mg of ultrapure water. Heat and stir to 90°C. After the polyvinyl alcohol 124 is completely dissolved, add 60.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 50 mg of CS-APB, and 2.5 mg of Alexa Fluor 488. Continue stirring at 90°C and 500 rpm for 2 hours. After cooling the stirred solution to room temperature, add 5.0 mg of pioglitazone hydrochloride. Continue stirring at 25°C and 500 rpm for 2 hours to obtain the drug-containing microneedle solution. Add the drug-containing microneedle solution to the microneedle mold, and evacuate for 1 minute to ensure the solution fully enters the needle holes of the mold. Continue adding solution until the mold is completely filled, and use a scraper to smooth the surface and remove excess solution. The mold containing the microneedle solution is left to stand at room temperature for 8–10 hours to allow the microneedles to initially take shape. Then, it is dried in a constant temperature drying oven at 35°C for 5–6 hours. After demolding and packaging, pioglitazone hydrogel microneedles are obtained.

[0102] Comparative Example 2-1

[0103] The microneedle preparation process is the same as in Example 2, except that the amount of microneedle auxiliary framework material is changed to be 1% lower than the minimum feed amount. Specifically, the total feed amount of microneedles is 500mg, including 2.5mg of pioglitazone hydrochloride, 3.0mg of polyvinyl alcohol 124, 60.0mg of poly(vinyl methyl ether-alt-maleic anhydride), 50mg of CS-APB, 2.5mg of Alexa Fluor 488, and 382mg of ultrapure water.

[0104] Comparative Example 2-2

[0105] The microneedle preparation process was the same as in Example 2, except that the amount of microneedle framework material was changed to be 12% lower than the minimum feed amount. Specifically, the total feed amount of microneedles was 500 mg, including 2.5 mg of pioglitazone hydrochloride, 5.0 mg of polyvinyl alcohol 124, 40.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 50 mg of CS-APB, 2.5 mg of Alexa Fluor 488, and 400 mg of ultrapure water.

[0106] Comparative Examples 2-3

[0107] The microneedle preparation process was the same as in Example 2, except that the amount of active pharmaceutical ingredient was changed to be 0.5% lower than the minimum feed amount. Specifically, the total feed amount of the microneedles was 500 mg, which included 1 mg of pioglitazone hydrochloride, 5.0 mg of polyvinyl alcohol 124, 60.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 50 mg of CS-APB, 2.5 mg of Alexa Fluor 488, and 381.5 mg of ultrapure water.

[0108] Example 3

[0109] This invention provides a method for preparing a pioglitazone hydrogel microneedle formulation. The total amount of microneedles is 500 mg, including 10.0 mg of pioglitazone hydrochloride, 10.0 mg of polyvinyl alcohol 124, 85.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 2.5 mg of sodium chloride, 100 mg of CS-APB, 5 mg of Alexa Fluor 488, and 287.5 mg of ultrapure water.

[0110] The specific process is as follows: Weigh 10.0 mg of polyvinyl alcohol 124 and add it to 287.5 mg of ultrapure water. Heat and stir to 90°C. After the polyvinyl alcohol 124 is completely dissolved, add 85.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 100 mg of CS-APB, and 5 mg of Alexa Fluor 488. Continue stirring at 90°C and 500 rpm for 2 hours. After cooling the stirred solution to room temperature, add 10.0 mg of pioglitazone hydrochloride and 2.5 mg of sodium chloride. Continue stirring at 25°C and 500 rpm for 2 hours to obtain the drug-containing microneedle solution. Add the drug-containing microneedle solution to the microneedle mold, and evacuate for 1 minute to ensure the solution fully enters the needle holes of the mold. Continue adding solution until the mold is completely filled, and use a scraper to smooth the surface and remove excess solution. The mold containing the microneedle solution is left to stand at room temperature for 8–10 hours to allow the microneedles to initially take shape. Then, it is dried in a constant temperature drying oven at 35°C for 5–6 hours. After demolding and packaging, pioglitazone hydrogel microneedles are obtained.

[0111] Comparative Example 3-1

[0112] The microneedle preparation process is the same as in Example 3, except that the amount of conductive material is changed to 0%. Specifically, the total amount of microneedles is 500 mg, including 10.0 mg of pioglitazone hydrochloride, 10.0 mg of polyvinyl alcohol 124, 85.0 mg of poly(vinyl methyl ether-alt-maleic anhydride) and 395.0 mg of ultrapure water.

[0113] Comparative Example 3-2

[0114] The microneedle preparation process was the same as in Example 3, except that the amount of conductive material was changed to be 0.5% higher than the maximum feed amount. Specifically, the total feed amount of the microneedles was 500 mg, which included 10.0 mg of pioglitazone hydrochloride, 10.0 mg of polyvinyl alcohol 124, 85.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 5.0 mg of sodium chloride, and 390.0 mg of ultrapure water.

[0115] Comparative Example 3-3

[0116] The microneedle preparation process is the same as in Example 3, except that the amount of active drug in the microneedles is changed to be less than 0.5%. Specifically, the total amount of microneedles is 500 mg, which includes 2.0 mg of pioglitazone hydrochloride, 10.0 mg of polyvinyl alcohol 124, 85.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 2.5 mg of sodium chloride, and 400.5 mg of ultrapure water.

[0117] Comparative Examples 3-4

[0118] The microneedle preparation process is the same as in Example 3, except that the amount of active drug in the microneedles is changed to be 2% higher than the maximum amount. Specifically, the total amount of microneedles is 500 mg, which includes 15.0 mg of pioglitazone hydrochloride, 10.0 mg of polyvinyl alcohol 124, 85.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 2.5 mg of sodium chloride, and 387.5 mg of ultrapure water.

[0119] Example 4

[0120] This invention provides a method for preparing a pioglitazone hydrogel microneedle formulation. The total amount of microneedles is 500 mg, including 10.0 mg of pioglitazone hydrochloride, 8.0 mg of polyvinyl alcohol 350, 80.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 2.5 mg of sodium chloride, 75 mg of CS-APB, 5 mg of Alexa Fluor 488, and 319.5 mg of ultrapure water.

[0121] The specific process is as follows: Weigh 8.0 mg of polyvinyl alcohol 350 and add it to 319.5 mg of ultrapure water. Heat and stir to 90°C. After the polyvinyl alcohol 350 is completely dissolved, add 80.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), 75 mg of CS-APB, and 5 mg of Alexa Fluor 488. Continue stirring at 90°C and 500 rpm for 2 hours. After cooling the stirred solution to room temperature, add 10.0 mg of pioglitazone hydrochloride and 2.5 mg of sodium chloride. Continue stirring at 25°C and 500 rpm for 2 hours to obtain the drug-containing microneedle solution. Add the drug-containing microneedle solution to the microneedle mold, and evacuate for 1 minute to ensure the solution fully enters the needle holes of the mold. Continue adding solution until the mold is completely filled, and use a scraper to smooth the surface and remove excess solution. The mold containing the microneedle solution is left to stand at room temperature for 8–10 hours to allow the microneedles to initially take shape. Then, it is dried in a constant temperature drying oven at 35°C for 5–6 hours. After demolding and packaging, pioglitazone hydrogel microneedles are obtained.

[0122] Comparative Example 4-1

[0123] The microneedle preparation process is the same as in Example 4, except that the type of microneedle skeleton material is changed and replaced with hydroxypropyl methylcellulose. Specifically, the total amount of microneedles fed is 500mg, which includes 10.0mg of pioglitazone hydrochloride, 8.0mg of polyvinyl alcohol 350, 80.0mg of hydroxypropyl methylcellulose, 2.5mg of sodium chloride, 75mg of CS-APB, 5mg of Alexa Fluor 488, and 319.5mg of ultrapure water.

[0124] Comparative Example 4-2

[0125] The microneedle preparation process is the same as in Example 4, except that the type of microneedle skeleton material is changed and replaced with polyvinylpyrrolidone K90. Specifically, the total amount of microneedles fed is 500 mg, which includes 10.0 mg of pioglitazone hydrochloride, 8.0 mg of polyvinyl alcohol 350, 80.0 mg of polyvinylpyrrolidone K90, 2.5 mg of sodium chloride, 75 mg of CS-APB, 5 mg of Alexa Fluor 488, and 319.5 mg of ultrapure water.

[0126] Example 5

[0127] This invention provides a method for preparing inner and outer electrolubricating gel patches. The total amount of the inner electrolubricating gel patch is 200 mg, including 10.0 mg of hydroxypropyl methylcellulose, 1 mg of sodium chloride, and 189 mg of ultrapure water. The total amount of the outer electrolubricating gel patch is 1000 mg, including 600 mg of glycerol, 120 mg of sodium polyacrylate, 5 mg of aluminum chloride, 0.8 mg of disodium EDTA, 20 mg of povidone, 30 mg of hydroxypropyl methylcellulose, 60 mg of gelatin, 8 mg of tartaric acid, and 156.2 mg of purified water.

[0128] The specific preparation process of the inner electrowetting gel patch is as follows: 10.0 mg of hydroxypropyl methylcellulose was weighed and added to 189 mg of ultrapure water. After heating and stirring for 2 hours until completely dissolved, 1 mg of sodium chloride was added, stirred thoroughly, and allowed to cool naturally at room temperature to obtain an electrowetting gel solution. The above solution was uniformly coated onto release film 1, dried at 60°C for 2 hours, and then laminated with release anti-adhesive film 2. The film was then cut into 1.6 × 1.6 cm pieces. 2 size.

[0129] The specific preparation process of the outer electrolubricating gel patch is as follows: 600 mg of glycerol, 120 mg of sodium polyacrylate, 5 mg of aluminum chloride, and 0.8 mg of disodium EDTA are weighed and mixed evenly under stirring to obtain the glycerol phase; 156.2 mg of purified water is taken, and 20 mg of povidone, 30 mg of hydroxypropyl methylcellulose, 60 mg of gelatin, and 8 mg of tartaric acid are added and dissolved under heating and stirring to obtain the aqueous phase; the aqueous phase is added to the glycerol phase under stirring until it is mixed evenly to form a gel, degassed, and the gel body is obtained. The gel is coated onto the anti-adhesive layer 1, dried at 45℃ for 2 hours, and then laminated with the anti-adhesive layer film 2. Then it is cut in two stages, with the diameter of the first cut being 5.6 × 5.6 cm larger than the diameter of the inner electrolubricating gel patch. 2 The patch was then cut, and a 1.6 x 1.6 cm section was removed from the cut patch. 2 The area is calculated to obtain an outer electrowetting gel patch with a hollow center.

[0130] Finally, the inner electrolubricating gel patch is placed in the center of the outer electrolubricating gel patch, and then the release liner 2 of the inner and outer electrolubricating gels is peeled off. A new release liner 2 is then laminated to obtain the electrolubricating gel patch.

[0131] Comparative Example 5-1

[0132] This invention provides a method for preparing inner and outer electrolubricating gel patches. The total amount of the inner electrolubricating gel patch is 200 mg, including 4.0 mg of hydroxypropyl methylcellulose and 196 mg of ultrapure water. The total amount of the outer electrolubricating gel patch is 1000 mg, including 200 mg of propylene glycol, 30 mg of sodium polyacrylate, 1 mg of aluminum hydroxide, 0.2 mg of calcium ethylenediamine acetate, 6 mg of carbomer, 4 mg of sodium carboxymethyl cellulose, 20 mg of polyvinyl alcohol 350, 2 mg of citric acid, and 736.8 mg of purified water.

[0133] The specific preparation process of the inner electrowetting gel patch is as follows: 4.0 mg of hydroxypropyl methylcellulose was weighed and added to 196 mg of ultrapure water. After heating and stirring for 2 hours until completely dissolved, the solution was allowed to cool naturally at room temperature to obtain an electrowetting gel solution. The solution was then uniformly coated onto release film 1, dried at 60°C for 2 hours, and then laminated with release anti-adhesive film 2. The resulting patch was cut into 1.6 × 1.6 cm pieces. 2 size.

[0134] The specific preparation process of the outer electrolubricating gel patch is as follows: 200 mg of propylene glycol, 30 mg of sodium polyacrylate, 1 mg of aluminum hydroxide, and 0.2 mg of calcium ethylenediamine acetate are weighed and mixed evenly under stirring to obtain the oil phase; 736.8 mg of purified water is taken, and 6 mg of carbomer, 4 mg of sodium carboxymethyl cellulose, 20 mg of polyvinyl alcohol 350 g, and 2 mg of citric acid are added and dissolved under heating and stirring to obtain the aqueous phase; the aqueous phase is added to the glycerol phase under stirring until it is mixed evenly to form a gel, degassed, and the gel body is obtained. The gel is coated onto the anti-adhesive layer 1, dried at 45℃ for 2 h, and then laminated with the anti-adhesive layer film 2. Then it is cut in two stages, with the diameter of the first cut being 5.6 × 5.6 cm larger than the diameter of the inner electrolubricating gel patch. 2 The patch was then cut, and a 1.6 x 1.6 cm section was removed from the cut patch. 2 The area is calculated to obtain an outer electrowetting gel patch with a hollow center.

[0135] Finally, the inner electrolubricating gel patch is placed in the center of the outer electrolubricating gel patch, and then the release liner 2 of the inner and outer electrolubricating gels is peeled off. A new release liner 2 is then laminated to obtain the electrolubricating gel patch.

[0136] Comparative Example 5-2

[0137] The preparation method of the inner electrolubricating gel patch is the same as in Example 5, except that the amount of gel skeleton material is changed. The total amount of electrolubricating gel layer is 200mg, including 20.0mg of hydroxypropyl methylcellulose and 180mg of ultrapure water.

[0138] The specific preparation process of the inner electrowetting gel patch is as follows: 20.0 mg of hydroxypropyl methylcellulose was weighed and added to 180 mg of ultrapure water. After heating and stirring for 2 hours until completely dissolved, the solution was allowed to cool naturally at room temperature to obtain an electrowetting gel solution. The solution was then uniformly coated onto release film 1, dried at 60°C for 2 hours, and then laminated with release anti-adhesive film 2. The resulting patch was cut into 1.6 × 1.6 cm pieces. 2 size.

[0139] Comparative Example 5-3

[0140] The preparation method of the inner electrolubricating gel patch is the same as that of Comparative Example 5-1, except that the amount of gel skeleton material was changed. The total amount of electrolubricating gel layer was 200 mg, including 2.0 mg of hydroxypropyl methylcellulose and 198 mg of ultrapure water.

[0141] The specific preparation process of the inner electrowetting gel patch is as follows: 2.0 mg of hydroxypropyl methylcellulose was weighed and added to 198 mg of ultrapure water. After heating and stirring for 2 hours until completely dissolved, the solution was allowed to cool naturally at room temperature to obtain an electrowetting gel solution. The solution was then uniformly coated onto release film 1, dried at 60°C for 2 hours, and then laminated with release anti-adhesive film 2. The resulting patch was cut into 1.6 × 1.6 cm pieces.2 size.

[0142] Comparative Example 5-4

[0143] The preparation method of the outer electrolubricating gel patch is the same as in Example 5, except that the amount of oil phase is changed. The total amount of the outer electrolubricating gel patch is 1000 mg, which includes 700 mg of glycerol, 140 mg of sodium polyacrylate, 6 mg of aluminum chloride, 1 mg of disodium EDTA, 20 mg of povidone, 30 mg of hydroxypropyl methylcellulose, 60 mg of gelatin, 8 mg of tartaric acid, and 35 mg of purified water.

[0144] The specific preparation process of the outer electrolubricating gel patch is as follows: 700 mg of glycerol, 140 mg of sodium polyacrylate, 6 mg of aluminum chloride, and 1 mg of disodium EDTA are weighed and mixed evenly under stirring to obtain the glycerol phase; 35 mg of purified water is taken, and 20 mg of povidone, 30 mg of hydroxypropyl methylcellulose, 60 mg of gelatin, and 8 mg of tartaric acid are added and dissolved under heating and stirring to obtain the aqueous phase; the aqueous phase is added to the glycerol phase under stirring until it is mixed evenly to form a gel, degassed, and the gel body is obtained. The gel is coated onto the anti-adhesive layer 1, dried at 45℃ for 2 hours, and then laminated with the anti-adhesive layer film 2. Then it is cut in two stages, with the diameter of the first cut being 5.6 × 5.6 cm larger than the diameter of the inner electrolubricating gel patch. 2 The patch was then cut, and a 1.6 x 1.6 cm section was removed from the cut patch. 2 The area is calculated to obtain an outer electrowetting gel patch with a hollow center.

[0145] Comparative Example 5-5

[0146] The preparation method of the outer electrolubricating gel patch is the same as that of Comparative Example 5-1, except that the amount of oil phase is changed. The total amount of the outer electrolubricating gel patch is 1000mg, including 100mg of propylene glycol, 10mg of sodium polyacrylate, 0.5mg of aluminum hydroxide, 0.1mg of calcium ethylenediamine acetate, 6mg of carbomer, 4mg of sodium carboxymethyl cellulose, 20mg of polyvinyl alcohol 350, 2mg of citric acid, and 857.4mg of purified water.

[0147] The specific preparation process of the outer electrolubricating gel patch is as follows: Weigh 100 mg of glycerol, 10 mg of sodium polyacrylate, 0.5 mg of aluminum chloride, and 0.1 mg of disodium EDTA and mix them evenly under stirring to obtain the glycerol phase; Take 857.4 mg of purified water, add 6 mg of carbomer, 4 mg of sodium carboxymethyl cellulose, 20 mg of polyvinyl alcohol, and 2 mg of citric acid, and dissolve them under heating and stirring to obtain the aqueous phase; Under stirring, add the aqueous phase to the glycerol phase until it is mixed evenly to form a gel, degas to obtain the gel body, coat the gel onto the anti-adhesive layer 1, dry at 45℃ for 2 h, and then laminate it with the anti-adhesive layer film 2. Then cut it in two stages, with the diameter of the first cut being 5.6 × 5.6 cm larger than the diameter of the inner electrolubricating gel patch. 2 The patch was then cut, and a 1.6 x 1.6 cm section was removed from the cut patch. 2 The area is calculated to obtain an outer electrowetting gel patch with a hollow center.

[0148] Comparative Examples 5-6

[0149] The preparation method of the outer electrolubricating gel patch is the same as in Example 5, except that the amount of aqueous phase is changed. The total amount of the outer electrolubricating gel patch is 1000 mg, which includes 600 mg of glycerol, 120 mg of sodium polyacrylate, 5 mg of aluminum chloride, 0.8 mg of disodium EDTA, 40 mg of povidone, 60 mg of hydroxypropyl methylcellulose, 100 mg of gelatin, 10 mg of tartaric acid, and 64.2 mg of purified water.

[0150] The specific preparation process of the outer electrolubricating gel patch is as follows: 600 mg of glycerol, 120 mg of sodium polyacrylate, 5 mg of aluminum chloride, and 0.8 mg of disodium EDTA are weighed and mixed evenly under stirring to obtain the glycerol phase; 64.2 mg of purified water is taken, and 40 mg of povidone, 60 mg of hydroxypropyl methylcellulose, 100 mg of gelatin, and 10 mg of tartaric acid are added and dissolved under heating and stirring to obtain the aqueous phase; the aqueous phase is added to the glycerol phase under stirring until it is mixed evenly to form a gel, degassed, and the gel body is obtained. The gel is coated onto the anti-adhesive layer 1, dried at 45℃ for 2 hours, and then laminated with the anti-adhesive layer film 2. Then it is cut in two stages, with the diameter of the first cut being 5.6 × 5.6 cm larger than the diameter of the inner electrolubricating gel patch. 2 The patch was then cut, and a 1.6 x 1.6 cm section was removed from the cut patch. 2 The area is calculated to obtain an outer electrowetting gel patch with a hollow center.

[0151] Comparative Examples 5-7

[0152] The preparation method of the outer electrolubricating gel patch is the same as that of Comparative Example 5-1, except that the amount of aqueous phase is changed. The total amount of the outer electrolubricating gel patch is 1000 mg, which includes 200 mg of propylene glycol, 30 mg of sodium polyacrylate, 1 mg of aluminum hydroxide, 0.2 mg of calcium ethylenediamine acetate, 3 mg of carbomer, 2 mg of sodium carboxymethyl cellulose, 10 mg of polyvinyl alcohol 350, 1 mg of citric acid, and 752.8 mg of purified water.

[0153] The specific preparation process of the outer electrolubricating gel patch is as follows: 200 mg of propylene glycol, 30 mg of sodium polyacrylate, 1 mg of aluminum hydroxide, and 0.2 mg of calcium ethylenediamine acetate are weighed and mixed evenly under stirring to obtain the oil phase; 752.8 mg of purified water is taken, and 3 mg of carbomer, 2 mg of sodium carboxymethyl cellulose, 10 mg of polyvinyl alcohol 350 mg, and 1 mg of citric acid are added and dissolved under heating and stirring to obtain the aqueous phase; the aqueous phase is added to the glycerol phase under stirring until it is mixed evenly to form a gel, degassed, and the gel body is obtained. The gel is coated onto the anti-adhesive layer 1, dried at 45℃ for 2 hours, and then laminated with the anti-adhesive layer film 2. Then it is cut in two stages, with the diameter of the first cut being 5.6 × 5.6 cm larger than the diameter of the inner electrolubricating gel patch. 2 The patch was then cut, and a 1.6 x 1.6 cm section was removed from the cut patch. 2 The area is calculated to obtain an outer electrowetting gel patch with a hollow center.

[0154] Optimization of process parameters for preparation of drug-loaded microneedle solution

[0155] This study investigated the effects of stirring temperature, speed, and time on drug release during the preparation of drug-containing microneedle solutions using single-factor experiments.

[0156] The preparation conditions used in Example 1 were as follows: heating and stirring at 90°C until polyvinyl alcohol 350 was completely dissolved, followed by the addition of poly(vinyl methyl ether-alt-maleic anhydride) and stirring for 2 hours, and finally stirring at 25°C at 500 r / min for 2 hours. The resulting drug-containing microneedle solution had moderate viscosity, was pale yellow, and was clear and transparent.

[0157] Comparative Examples 1-1 to 1-3 adjusted the stirring temperature after drug addition (35℃, 45℃, 55℃), and the viscosity of the resulting drug-containing microneedle solutions did not change significantly; they were all pale yellow and transparent, and had no effect on the preparation of microneedles.

[0158] Comparative Examples 1-4 to 1-6 varied the stirring speed (250 r / min, 750 r / min, and 1000 r / min). The results showed that excessively high stirring speeds (Comparative Examples 1-6) led to the generation of a small number of bubbles in the drug-containing microneedle solution, increasing the viscosity of the microneedle solution and affecting the microneedle preparation effect. In particular, Comparative Examples 1-5 and 1-6 showed significant bubble generation and increased viscosity, resulting in material waste and demonstrating the rationality of the 500 r / min stirring speed used in Example 1.

[0159] Comparative Examples 1-7 to 1-9 varied the stirring time (1 h, 3 h, 4 h). The results showed that the drug-containing microneedle solution obtained with a shorter stirring time (Comparative Example 1-7) was slightly turbid compared to Example 1, indicating incomplete drug encapsulation. The longer stirring time (Comparative Examples 1-8 and 1-9) resulted in the generation of a small number of bubbles in the drug-containing microneedle solution, increasing the viscosity of the solution and affecting the microneedle preparation effect.

[0160] In summary, the preparation conditions in Example 1, particularly the stirring temperature of 90°C, stirring speed of 500 r / min, and stirring time of 2 h, have proven to be optimal, ensuring both high drug loading and avoiding material waste during the preparation process. These findings validate the rationality of the parameter settings in the sample preparation process of Example 1, providing important experimental evidence for the efficient preparation and application of hydrogel microneedles.

[0161] Mechanical strength testing of microneedle materials

[0162] This study focuses on the dosage optimization and evaluation of various excipients used in microneedles, using the mechanical strength of the needle tip as the evaluation criterion. The specific experimental process is as follows:

[0163] Compression tests were conducted using a calibrated physical property tester equipped with a P / 25 probe. The mechanical strength of different microneedles was measured, and force-displacement curves were obtained to compare the tip load of the microneedles under different material dosages. During the test, the upper probe moved towards the microneedle array at a speed of 0.05 mm / sec, the probe trigger force was set to 0.049 N, and the maximum compression distance was 1 mm. Once the needle tip contacted the stainless steel plate, the tester recorded the instantaneous force and displacement every 0.2 s. During the period when the probe touched the needle tip and applied pressure, the relevant data was transmitted to the electronic information control system until the probe reached the preset maximum compression distance, after which data recording automatically stopped and the system reset to the starting position. The relevant results are presented in [the table / document / etc.]. Figure 1 .

[0164] The results of the needle tip mechanical strength evaluation are as follows: the microneedles of Examples 2 and 3, as well as Comparative Examples 2-1, 2-2, 3-1, and 3-2, all underwent compression testing to quantify their tip mechanical strength. Test results using a physical property testing instrument showed that the microneedles of Examples 2 and 3 exhibited higher breaking forces of 27N and 38N, respectively, significantly higher than the 20N and 16N of Comparative Examples 2-1 and 2-2. This indicates that appropriately increasing the amount of skeleton material and auxiliary skeleton material can significantly improve the mechanical strength of the microneedles.

[0165] Example 2 achieved optimized mechanical properties by using 60.0 mg of poly(vinyl methyl ether-alt-maleic anhydride), while Comparative Example 2-2, which reduced the amount of this material, exhibited lower mechanical strength.

[0166] Example 3 further increased the amount of poly(vinyl methyl ether-alt-maleic anhydride) to 85.0 mg, achieving higher breaking strength and exceeding the upper limit of 85.0 mg. As in Comparative Example 3-2, further increasing to 90.0 mg did not significantly improve mechanical strength, indicating that there is an optimization point in the amount of material used. Beyond this point, the improvement in mechanical strength is no longer significant.

[0167] Evaluation of the electrical conductivity and water solubility properties of drug-containing microneedle solutions

[0168] This invention determined the solubility of pioglitazone hydrochloride in different solvents and tested the conductivity of drug-containing microneedle solutions based on the effect of different amounts of conductive material. Specifically, 500 mg of microneedle solution was added to a mold measuring 1.5 × 1.5 × 0.75 cm, and the current was measured by inserting the electrodes of a directional drug delivery device (a device for in vitro iontophoresis experiments) into the solution. By comparing the effects of different amounts of sodium chloride on conductivity in Examples 1, 3, and Comparative Examples 3-1 and 3-2, the appropriate range of conductive material addition was optimized.

[0169] The experimental results are shown in Table 1. It can be seen that in the drug-containing microneedle solution, as the amount of sodium chloride increased from 0% (Comparative Example 3-1) to 0.3% (Example 1) and further to 0.5% (Example 3), the conductivity of the solution gradually increased with the increase of the conductive material. After reaching 0.5% (Comparative Example 3-2), the amount of conductive material further increased, while the conductivity of the drug-containing microneedle solution remained stable without a significant upward trend. That is, with the microneedle material of the present invention, at this concentration, sodium chloride ions (Na+) and chloride ions (Cl-) reach equilibrium, achieving the conductivity saturation effect of the ionic solution.

[0170] In addition, the conductivity of three different microneedle framework materials, namely Example 4, Comparative Example 4-1, and Comparative Example 4-2, was tested. The results showed that the material poly(vinyl methyl ether-alt-maleic anhydride) had good conductivity, while the material hydroxypropyl methylcellulose also had some conductivity, but not as good as poly(vinyl methyl ether-alt-maleic anhydride), and polyvinylpyrrolidone K90 had virtually no conductivity.

[0171] Table 2 shows the solubility of the drug in different solvents. The solubility of PIO in the P(MVE-alt-MAH) solution is significantly higher than in other solutions, indicating that this polymer has a strong solubilizing effect on the drug. This may be due to hydrogen bonds or other non-covalent interactions between P(MVE-alt-MAH) and PIO, or the formation of self-assembled structures such as micelles by the polymer, which encapsulate drug molecules, thereby increasing their apparent solubility and drug loading.

[0172] Table 1

[0173]

[0174] Table 2

[0175]

[0176] Characterization and performance evaluation of hydrogel microneedles

[0177] Based on the optimization of pioglitazone hydrogel microneedles, this study uses Example 4 as an example to characterize and evaluate the performance of the hydrogel microneedle portion in the claims of this invention, mainly covering the microneedle's appearance, puncture capability, and swelling characteristics.

[0178] Microneedle Appearance Characterization: In this study, macroscopic photographs of the microneedles from Embodiment 4 were taken using a digital camera; then, the microstructure of the microneedles was observed using an MP 16× magnification lens; finally, the microneedles were sputtered with gold and scanned using a SEM (JEOL JSM-IT200). The results are as follows: Figure 2 As shown, the microneedles are neatly arranged in an array, with no empty needles or air bubbles, and the needle surface is undamaged, with an intact appearance.

[0179] Microneedle puncture performance evaluation: Frozen rat skin samples were thawed with physiological saline, washed, and dried with filter paper before being fixed onto a polystyrene foam board. The microneedles from Example 4 were inserted into the skin samples with a force of 10 N for 3 minutes, then removed. The skin samples were then placed in 4% paraformaldehyde for 24 hours and fixed with paraffin. To further analyze the penetration effect of the microneedles, the obtained samples were sectioned and stained using hematoxylin-eosin (HE) staining. Simultaneously, to more thoroughly evaluate the ability of the microneedles to penetrate the stratum corneum and enter intradermal tissue, the skin punctured by the microneedles was stained with 0.4% trypan blue. The results are as follows: Figure 3 As shown. Figure 3 a and Figure 3 Figure b shows the skin at the microneedle puncture site stained blue after trypan blue staining; Figure 3 Figure c shows rat skin stained with hematoxylin and eosin (HE), where pinholes formed after the microneedles penetrate are clearly visible. These results validate the ability of the example microneedles to penetrate the stratum corneum.

[0180] Microneedle swelling performance: The microneedles prepared in Example 4 were cut into small pieces, and six pieces were then attached to the back skin of finely shaved rats. Each piece was pressed for 30 seconds and fixed with 3M tape. Subsequently, at 0 min, 5 min, 10 min, 30 min, 45 min, and 60 min, a microneedle sample was removed and observed under a 4× objective lens. For in vitro swelling tests, the microneedle tips were immersed in PBS solution with a pH of 7.4, and removed at 0, 10, 20, 30, 45, and 60 seconds. The samples were then blotted dry with filter paper and observed and analyzed under a 4× objective lens.

[0181] The swelling characteristics results are as follows Figure 4 As shown in a and Table 3, within the initial 1 minute, the microneedles maintained their original shape in the rats; after 5 minutes, the tips of the microneedles gradually lost sharpness, marking the beginning of the swelling process. Between 10 and 45 minutes, the swelling softened the microneedles, causing the tips to bend when removed from the animal's skin; by 60 minutes, the entire microneedle tip showed signs of swelling, with blurred edges. The in vitro swelling behavior differed significantly from the in vivo behavior, such as... Figure 4 As shown in b and Table 4, the microneedles rapidly begin to swell upon contact with the pH 7.4 PBS solution, with a significant increase in volume after 30 seconds. Further observation revealed that the swelling rate significantly decreased between 45 and 60 seconds, until it completely stopped. Overall, the microneedles of this invention exhibit excellent swelling properties. However, in practical applications, appropriate pretreatment is necessary to ensure rapid swelling and proper functioning of the microneedles.

[0182] Table 3. Changes in the swelling length of microneedles in vivo.

[0183]

[0184]

[0185] Table 4. Changes in the in vitro swelling length of microneedles

[0186]

[0187] Evaluation of drug delivery characteristics of microneedles

[0188] Drug loading determination: The tip portion of the microneedles prepared in Example 4 was separated using a scraper, and both the tip and the backing portion were immersed in 80% methanol solution for 48 hours to fully extract the drug. After immersion, solid residues were removed by filtration, and the filtrate was then analyzed by high-performance liquid chromatography (HPLC) to accurately determine the drug loading of the microneedles. The results showed that the drug loading of the microneedle tip was 0.7 mg, while the drug loading of the backing portion was 4.3 mg, and the relative standard deviations (RSDs) of both were less than 5%, indicating the accuracy and repeatability of the drug extraction process and the determination method.

[0189] Drug distribution uniformity assessment: The microneedle product of Example 4 was uniformly divided into 9 parts, and five parts from the four corners and the center were taken for testing. Similarly, these parts were immersed in 80% methanol solution for 48 hours, followed by filtration and HPLC analysis. The results of drug distribution uniformity are listed in Table 5, showing that the relative standard deviations (RSDs) within the microneedle groups were 9.07%, 7.65%, and 7.26%, all less than 10%. Since both the tip and backing of the microneedles of this invention are drug-loaded, and pioglitazone hydrochloride itself has high safety and a wide dosage range, an RSD of 10% was used as the standard evaluation, indicating that the drug distribution within the microneedles is relatively uniform. Furthermore, the inter-group RSD value was 2.21%, less than 5%, demonstrating the consistency of drug loading in different batches of microneedles.

[0190] Table 5

[0191]

[0192] Conductivity and adhesion of electrolubricating gel patches

[0193] The inner gel layer of the electrolubricating gel patch provides a water source, solving the problem of low skin moisture and long expansion time for microneedles without external water. Therefore, the inner gel layer needs good formability and a certain degree of conductivity, while the outer gel layer provides skin-friendly adhesion, bonding the skin to the smart wearable device to form a complete pioglitazone hydrochloride smart drug delivery system, which also requires good adhesion. Seven electrolubricating gel patch samples were prepared according to Example 5 and Comparative Examples 5-1 to 5-7. Electrodes of a directional transdermal drug delivery device were connected to the front and back of the inner gel layer, respectively. The differences in conductivity of different inner electrolubricating gel layer formulations were compared to investigate the dosage range of gel skeleton material and conductive material in the electrolubricating gel layer. In addition, the adhesion performance of the outer gel patch was evaluated by initial tack and holding tack. The results are shown in Table 6. Increasing the gel skeleton material did not significantly affect the conductivity, but excessive skeleton material (Comparative Example 5-2) affected the texture of the gel, making it too hard and lacking in softness. Conversely, if the gel matrix material is insufficient (Comparative Example 5-3), the inner electrolubricating gel patch cannot be effectively formed. Similarly, too much oil phase material or too little aqueous phase material in the outer layer can also cause problems such as the gel failing to form and poor adhesion.

[0194] Adding conductive materials significantly increases the conductivity of the electrowetting gel layer, but for safety reasons, the dosage of conductive materials is controlled within the range of 0%-0.5%.

[0195] Table 6

[0196]

[0197]

[0198] Figure 5 The comparison of transdermal permeability between Example 4 with and without the electrowetting gel layer (Example 5) shows that the amount of drug permeation increased significantly after adding the electrowetting layer, especially the drug permeation time was shortened and the drug permeation was accelerated. This proves that ensuring the electrowetting gel layer of the microneedle accelerates the hydration of the gel microneedle, which is beneficial to drug permeation.

[0199] In vitro permeation characteristics of microneedle combined with iontophoresis drug delivery system

[0200] The pioglitazone hydrogel microneedles of Example 3 and Comparative Examples 3-1, 3-2, 3-3, and 3-4 were subjected to in vitro skin permeation experiments on rats. Within the scope of claim 1, the permeability of different active drug concentrations under in vitro skin permeation was investigated. During the experiment, each microneedle was cut into 7×7 needle fragments to suit the size of the diffusion cell pores, with an area of ​​approximately 45.6 mm². 2The drug loading capacity is approximately 1.60 mg (approximately 0.15 mg at the needle tip and approximately 1.45 mg on the backing). Prepared and frozen rat skin was thawed in physiological saline for 3-5 minutes. Microneedles were inserted into the rat's dorsal skin with a force of 10 N, pressing for 1 minute and aligning the skin with the receptor chamber pores, with the stratum corneum facing outwards. Then, an electrode patch covered with an electrolubricating gel was fixed and connected to the positive electrode of the targeted transdermal drug delivery device. The negative electrode of the targeted transdermal drug delivery device was connected to the receiving liquid to form a pathway, such as... Figure 6 As shown.

[0201] 20% PEG-NS was selected as the receiving solution, and 5.0 ml was added to the recipient chamber, ensuring no air bubbles formed at the skin contact point. A constant-temperature circulating water bath was connected outside the recipient chamber at 32℃. Then, at 2, 4, 6, and 8 hours, 1 ml of the receiving solution was taken from the recipient chamber and 1 ml of 20% PEG-NS was added. After centrifugation, the skin receiving solution samples at each time point were filtered through a 0.22 μm filter membrane, and the filtrate was injected. The peak area was determined by HPLC, and the concentration was calculated using the external standard method. The cumulative permeability Qi (μg·cm³) per unit area was calculated according to the following formula. -2 ).

[0202]

[0203] Note: Qi is the cumulative penetration area per unit area after several hours, Ci represents the drug concentration, Vi is the volume of the receiver solution each time, and S is the effective penetration area. In this experiment, V = 5 mL, S = 0.77 cm², and Vi = 1 mL.

[0204] The transdermal permeation curve of pioglitazone hydrochloride was obtained by plotting Qi against t, as shown below. Figure 6 , 7 As shown in Figure 8. Figure 7 The transdermal permeation curves of Example 3 and its comparative examples 3-1 and 3-2 are shown. The results indicate that within the salt ion concentration range of 0%-1.0%, the permeation volume and rate at a salt ion concentration of 0.5% are higher than those at 0% and 1%. Analysis of the results suggests that, since both sodium ions and pioglitazone hydrochloride are cations, the movement of sodium ions under electromigration forms an electroosmotic flow, driving the permeation of pioglitazone hydrochloride and further enhancing its permeability beyond the existing electromigration capacity. Furthermore, an appropriate amount of salt ions can increase the conductivity of the microneedles. When the salt ion concentration is too high, the ionized salt ions compete with drug molecules, thereby reducing the drug permeation rate. This explains why the permeation volume of the microneedles in Comparative Example 3-2 is lower than that in Comparative Example 3-1. Figure 8The transdermal permeation curves for Example 3 and its comparative examples 3-3 and 3-4 are shown. The results indicate that within a drug loading range of 0.5%–2.0%, the cumulative permeation per unit area of ​​the microneedles is directly proportional to the drug loading concentration, with the highest permeation occurring at a drug loading concentration of 2.0%. Furthermore, when the drug loading exceeds 2%, the drug cannot be completely dissolved in the blank microneedle solution. All experiments were conducted under a 0.5 mA current condition. Figure 9 The figures show the transdermal permeation curves obtained by applying different current magnitudes for Example 3. The results show that within 8 hours, the permeation rate was significantly higher when the current was 0.5 mA than when it was 0.1 mA and 0.3 mA. Furthermore, within the current range of 0.1-0.5 mA, the ex vivo skin permeation capacity was positively correlated with the current intensity, and 0.5 mA is within the safe current intensity range for drug delivery, and will not cause safety issues. Figure 10 The figure shows the percutaneous permeation curve obtained by extending the in vitro skin permeation time for Example 3. The results show that the cumulative permeation per unit area in both the ionization group and the normal group is positively correlated with time. The ionization group significantly increased the percutaneous permeation of pioglitazone hydrochloride (P<0.01), indicating that iontophoresis technology can continuously help drugs penetrate the skin. Figure 11 To investigate the effect of different drug concentrations on ex vivo skin penetration in Examples 4, 3-3, and 3-4, the results showed that when the drug concentration was below 0.5%, the permeation was too low to achieve an effective therapeutic dose. Conversely, when the drug concentration exceeded 2%, the overall permeation decreased, potentially leading to reduced drug formulation stability, possibly related to drug overload.

[0205] The effect of whether the backing contains medication on drug penetration

[0206] To investigate the effect of drug-containing backing on drug penetration, Example 4 (drug-containing microneedles + drug-containing backing) was used as the control group. A blank backing layer (without drug) was prepared according to Example 1. Experimental groups (drug-containing microneedles + drug-free backing) were then formed. Following standard operating procedures, the microneedles in each group were subjected to ex vivo skin penetration experiments under iontophoresis conditions. The results are shown in the table below. Figure 12 The drug penetration of the control group (with drug-containing backing) was significantly higher than that of the experimental group (without drug-containing backing), indicating that the drug in the backing layer can also penetrate into the skin through the microneedle channels under iontophoresis conditions, significantly increasing the transdermal drug penetration and compensating for the problem of insufficient drug loading at the microneedle tip.

[0207] Drug diffusion in vivo studies

[0208] To simulate the diffusion of pioglitazone hydrochloride in the skin, rhodamine B, a fluorescent substance with a similar molecular weight and also cationic, was selected as a substitute to simulate in vivo drug diffusion. 2.0 g of blank microneedle solution was mixed with 100 μL of 2 mg / mL rhodamine B, and centrifuged at 6000 r / min for 10 min to remove air bubbles, ensuring uniform distribution of rhodamine B, thus preparing fluorescent microneedles.

[0209] Six SD rats were used, with three in the experimental group and three in the control group. Hair was removed from the back and sides of both groups of rats, and they were anesthetized by intraperitoneal injection of urethane at a dose of 750 mg / kg. Fluorescent microneedles were inserted vertically into the skin on the back of the rats with a force of 10 N, and immobilized after 1 minute of pressure. The microneedles in the experimental group were connected to a targeted drug delivery device with a maximum current of 0.5 mA; the microneedles in the control group were also connected to the same device with a maximum current of 0 mA. The fluorescence intensity and diffusion range of the experimental and control groups were observed and compared at 3 min and 30 min using an in vivo imaging system (IVIS LuminaLT, Series III) to evaluate the effect of ionization on promoting drug diffusion.

[0210] like Figure 13 As shown, at 3 minutes, the radiance of the experimental group was 6.76 × 10⁻⁶. 9 The control group was 7.81 × 10⁻⁶. 9 At 30 minutes, the radiance of the experimental group was 2.69 × 10⁻⁶. 10 The control group was 1.15 × 10⁻⁶. 10 The radiance increased by 4.0 times and 1.5 times compared to the 3-minute mark, respectively. Analysis of the images and data revealed that the electroosmotic effect was not significant in the early stages of diffusion. Combined with in vivo microneedle swelling experiments, this was mainly because the microneedles did not fully absorb water and swell at 3 minutes, resulting in insufficient conductivity. After 30 minutes of diffusion, the swollen portion of the microneedles increased, the microneedle penetration pore size increased, and the conductivity increased, thereby promoting the electromigration of drug molecules in the ionized group and significantly improving the drug diffusion efficiency. These simulation results provide a reference for the in vivo diffusion process of pioglitazone hydrochloride.

[0211] In vivo pharmacodynamic experiment in type 2 diabetic rats

[0212] 1. Test Methods

[0213] This study selected the change in fasting blood glucose before and after drug administration as the efficacy indicator. The specific procedure is as follows:

[0214] Before administration: Fasting blood glucose was measured in all rats, followed by a normal 1-hour feeding, then fasting and administration.

[0215] Six hours after administration: The rats were in a fasting state, and their fasting blood glucose was measured again. The change in blood glucose (Δmmol / L) was defined as the difference in fasting blood glucose before and after administration, and the calculation formula was Δmmol / L = AB, where A is the fasting blood glucose before administration and B is the fasting blood glucose after administration.

[0216] The experimental groups included a positive control group, a conductive microneedle experimental group, and a model group, with 6 type II diabetic rats in each group.

[0217] Model group: No processing is performed; it is used only as an evaluation control.

[0218] Positive control group: Commercially available pioglitazone hydrochloride tablets were used as the positive control, with a daily dose of 4.0 mg / kg administered by gavage for 8 consecutive days. This dose was determined based on the results of a preliminary experiment to ensure that blood glucose levels in the model mice were effectively reduced.

[0219] Conductive microneedle test group: Administered medication daily for eight consecutive days via conductive microneedles as described in Example 4, with a dose of 50 mg / kg each time. The specific procedure is as follows:

[0220] In Example 4, the microneedles were placed on the shaved area of ​​the rat's back, and the microneedles were pressed with a force of approximately 10 N for 3 minutes to allow the microneedles of the gel microneedle patch to penetrate the skin. An electrolubricating gel patch was then placed over the microneedles, and the smart wearable device was worn over the electrolubricating gel patch. The power button was pressed to initiate smart drug delivery, and the microneedles were replaced daily.

[0221] 2. Test Results

[0222] As shown in Table 7, within 8 days of administration, the Δ values ​​for both the positive control group and the experimental group were greater than 0, while the Δ values ​​for the model group were less than 0. This indicates that blood glucose levels in both the positive control group and the experimental group showed a decreasing trend after administration, while blood glucose levels in the model group showed an increasing trend. After 6 days, the Δ value in the conductive microneedle experimental group was greater than that in the positive control group, indicating that the blood glucose decrease in the experimental group was superior to that in the positive control group and other groups (P<0.05). The results demonstrate that microneedle combined with iontophoresis has a good therapeutic effect during these 8 consecutive days of administration. Furthermore, according to... Figure 14 It is evident that after microneedle administration, the blood glucose levels in diabetic rats showed no significant diurnal fluctuations but rather a slow decreasing trend. This is related to the sustained-release effect of the drug after microneedle combined with iontophoresis. The Δ values ​​in the model group were all less than 0, indicating no decreasing trend in blood glucose. This suggests that, excluding drug administration factors, the fasting blood glucose levels in diabetic rats under this experimental environment were higher after drug administration than before. The pharmacodynamic results demonstrate the significant role of iontophoresis in the development of transdermal pioglitazone hydrochloride administration.

[0223] Table 7

[0224]

[0225] Skin irritation test

[0226] 1. Test Methods

[0227] The rats' backs were shaved, with a fine shave. The gel microneedle patch from Example 4 was placed on the shaved area and pressed with approximately 10 N for 3 minutes to allow the microneedles to penetrate the skin. An electrolubricating gel patch was then placed over the microneedles, and the smart wearable device was worn over the patch. The power button was pressed to initiate smart drug delivery, and the microneedles were replaced daily. Skin condition at the drug delivery site was recorded and observed before drug administration and at 0h, 6h, 24h, and 48h after drug withdrawal. Furthermore, after 8 days of continuous drug administration, skin tissue from the drug delivery site was sectioned and stained for observation to assess the safety of the microneedles.

[0228] 2. Test Results

[0229] like Figure 15 As shown, obvious erythema was visible at the application site after drug withdrawal, caused by microneedle penetration into the skin. Six hours after drug withdrawal, the application site had largely returned to normal, with no obvious erythema. Twenty-four hours after drug withdrawal, the skin had fully recovered. Forty-eight hours later, the skin condition was normal, with no recurrence of erythema, edema, or other symptoms. This was confirmed by skin tissue section analysis. Figure 16 (Left: Normal skin tissue; Right: Skin tissue at the administration site) As can be seen, after 8 days of continuous administration, the rat skin tissue showed no significant difference from normal skin tissue, and no inflammation was observed. The results indicate that although microneedle puncture causes short-term skin erythema, the skin has a rapid recovery capacity, demonstrating the system's advantage in terms of skin safety.

[0230] Wearable device design

[0231] This invention provides a design scheme for a smart wearable device, the electronic schematic of which is shown below. Figure 17 As shown. The core control unit of the system is a microcontroller unit (MCU), which is responsible for coordinating the work of various functional modules. The upper area of ​​the device integrates a Bluetooth module and a display screen. The Bluetooth module enables the wireless transmission of real-time blood glucose data, synchronizing the monitoring results to the user's smartphone or other mobile terminals, supporting remote data monitoring and analysis; the display screen intuitively displays the current blood glucose level, medication status, and device operation status, allowing users to understand their health status in real time.

[0232] The right side of the device houses the blood glucose detection module, which incorporates a biosensor element. This element uses a microneedle array to collect real-time glucose concentration data from the interstitial fluid of the skin. The sensor utilizes the fluorescence resonance energy transfer (FRET) principle, leveraging energy transfer between a fluorescent marker on the microneedle patch and a receptor to monitor blood glucose levels in real time. These biosignals are converted into electrical signals and transmitted to the MCU for data processing and analysis. The MCU's built-in algorithm analyzes the collected blood glucose data in real time to determine if the blood glucose level exceeds a preset safety threshold.

[0233] When blood glucose levels exceed 10.0 mmol / L for 3 consecutive hours, or remain between 7.2 and 10 mmol / L for 8 consecutive hours, the MCU determines that drug delivery needs to be initiated based on a preset control algorithm and automatically activates the drug delivery module with iontophoresis function. This module provides the necessary electrical energy to the pioglitazone hydrogel microneedle patch via microcurrent, promoting transdermal drug absorption. The system dynamically adjusts the current intensity and delivery duration based on real-time blood glucose levels to ensure on-demand drug release, precisely control the dosage, avoid overdose or underdose, and ensure treatment safety and effectiveness.

[0234] The outer gel layer of the smart device provides skin-friendly adhesion, ensuring close contact between the microneedle array and the skin, while maintaining a stable connection between the device and the skin to prevent loosening or detachment during drug delivery. The power supply is provided by a built-in battery and energy management module, offering a stable power source and a low-battery warning function to ensure the device can operate normally in critical situations.

[0235] Most of the device's functions are automated, requiring only initial configuration by the user, with no frequent intervention needed thereafter, thus enhancing ease of use and comfort. Furthermore, the device includes a manual operation option, allowing users to manually adjust dosing parameters or pause automatic dosing in special circumstances via a mobile application, further enhancing system flexibility and user control.

[0236] Through the above design, the intelligent wearable device of this invention not only realizes real-time blood glucose monitoring and automatic drug delivery, but also provides a safe, convenient, and efficient personalized diabetes management solution through intelligent data processing and user interaction design. This solution aligns with the trend of precision medicine and personalized medicine in modern healthcare, reducing patients' reliance on traditional monitoring and drug delivery methods while ensuring treatment effectiveness and improving the convenience and comfort of treatment.

[0237] Smart Wearable Unit Module Testing

[0238] The study verified the accuracy and reliability of the biosensor in the blood glucose detection module for measuring blood glucose.

[0239] Blood glucose levels were measured in normal and diabetic rats using standardized blood glucose meters. A biosensor was attached to the dorsal skin of the same rat (the dorsal skin was shaved before being used as a microneedle in this example), and the biosensor readings were recorded and compared with those of a standard blood glucose meter. The performance of the sensor under different standard conditions was evaluated. The results are shown in Table 8 below.

[0240] Table 8

[0241]

[0242] The above experimental results show that the readings of the FRET sensor in the intelligent device should be consistent with those of the standard instrument, and the error range should be within acceptable limits (blood glucose error range ±15%). This experiment demonstrates that the blood glucose detection module in the intelligent drug delivery system can meet the designed technical specifications and functional requirements.

Claims

1. A pioglitazone hydrochloride microneedle drug delivery system for the treatment of type II diabetes, characterized in that: The system includes: a pioglitazone hydrochloride hydrogel microneedle patch; The pioglitazone hydrochloride hydrogel microneedle patch comprises, by weight, 0.5%-2.0% pioglitazone hydrochloride, 12%-17% microneedle skeleton material, 1%-2% microneedle auxiliary skeleton material, 0%-0.5% conductive material, 10%-20% glucose responsive material, 0.5%-1% fluorescent material, and 57.5%-76% ultrapure water.

2. The pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes according to claim 1, characterized in that: The microneedle skeleton material is poly(vinyl methyl ether-alt-maleic anhydride); The microneedle auxiliary skeleton material is selected from one of polyvinyl alcohol 124 and polyvinyl alcohol 350; The conductive material is sodium chloride; The glucose responsive material is chitosan-phenylboronic acid derivative (CS-APB); The fluorescent material uses one of Alexa Fluor 488 and Alexa Fluor 568 as a fluorescent donor and uses Rhodamine B fluorescent acceptor. The fluorescent donor and the fluorescent acceptor are mixed in a molar ratio of 2:

1.

3. The pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes according to claim 1, characterized in that: The system further comprises: An electrowetting gel patch, comprising an inner layer and an outer layer; the inner layer comprises, by weight, 2.0-5.0% of a gel skeleton material, 0%-0.5% of a conductive material, and 94.5%-98% of ultrapure water; the outer layer comprises, by weight, 3-12% of a matrix skeleton material, 0.1-0.5% of a crosslinking agent, 20-60% of a moisturizing agent, 1-5% of a viscosity enhancer, 2-6% of an excipient, 0.2-0.8% of a crosslinking regulator, 0.02-0.08% of a complexing agent, and 15.62-73.68% of ultrapure water; Smart wearable devices, including blood sugar detection modules and drug delivery modules; The blood glucose detection module is used to use the fluorescent material in the pioglitazone hydrochloride hydrogel microneedle patch to monitor the changes in blood glucose concentration in the interstitial fluid of the skin in real time through the FRET technology. When the blood glucose concentration is detected to be higher than a preset threshold, the blood glucose detection module transmits an iontophoresis start signal to the drug delivery module; The drug delivery module is used to, after receiving the iontophoresis signal from the blood glucose detection module, wet the pioglitazone hydrochloride hydrogel microneedle patch through the electrowetting gel patch, thereby achieving transdermal absorption of pioglitazone hydrochloride with the assistance of iontophoresis.

4. The pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes according to claim 3, characterized in that: The gel skeleton material is hydroxypropyl methylcellulose; The matrix skeleton material is partially neutralized sodium polyacrylate; The cross-linking agent is one or more of aluminum chloride, aluminum hydroxide, and aluminum glycolate mixed in any proportion; The moisturizing agent is glycerin or propylene glycol; The viscosity enhancer is one or more of povidone, hypromellose, carbomer and sodium carboxymethylcellulose mixed in any proportion; The excipient is gelatin or polyvinyl alcohol; The cross-linking regulator is tartaric acid or citric acid; The complexing agent is disodium ethylenediaminetetraacetate or calcium sodium ethylenediamine acetate.

5. The pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes according to claim 3, characterized in that: A first release anti-adhesion film and a second release anti-adhesion film are respectively arranged on both sides of the electrowetting gel layer patch; the release force of the first release anti-adhesion film is greater than the release force of the second release anti-adhesion film; When in use, the electrowetting gel layer patch can be connected to the smart wearable device after the first release anti-adhesive film is peeled off, and the electrowetting gel layer patch can be connected to the pioglitazone hydrochloride hydrogel microneedle patch after the second release anti-adhesive film is peeled off.

6. The pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes according to claim 3, characterized in that: The drug delivery process of the pioglitazone hydrochloride microneedle drug delivery system includes: The blood glucose threshold is set as blood glucose continuously exceeding 10.0mmol / L within 3 hours or blood glucose continuously between 7.2 and 10mmol / L within 8 hours; The pioglitazone hydrochloride microneedle needle tip is inserted into the skin, and then the electro-wetting gel patch with the second release anti-adhesive film torn off is attached to the outside of the pioglitazone hydrochloride microneedle patch, and then the first release anti-adhesive film of the electro-wetting gel patch is torn off; The smart wearable device is worn outside the electrohydrating gel patch. The blood glucose detection module of the smart wearable device uses the fluorescent material in the pioglitazone hydrochloride hydrogel microneedle patch to monitor the changes in blood glucose concentration in the skin interstitial fluid in real time through the FRET technology. When the blood glucose concentration is detected to be higher than the preset threshold, the blood glucose detection module transmits an iontophoresis start signal to the drug delivery module; after the iontophoresis is started, the drug delivery module adjusts the current to achieve the precise release of pioglitazone hydrochloride.

7. A method for preparing a pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes, characterized in that: The preparation process of the pioglitazone hydrochloride hydrogel microneedle patch includes: Prepare a blank microneedle solution: prepare a blank microneedle solution by weight percentage, specifically including 12%-17% of microneedle skeleton material, 1%-2% of auxiliary skeleton material, 10%-20% of glucose response material, 0.5%-1% of fluorescent material and 57.5%-76% of ultrapure water; fully stir all the above ingredients until they are completely dissolved, then add 0%-0.5% of conductive material to the mixed solution, continue stirring until the conductive material is completely dissolved, and obtain a blank microneedle solution; Preparation of drug-containing microneedle solution: adding 0.5%-2.0% pioglitazone hydrochloride to the blank microneedle solution to form a uniform drug-containing microneedle solution; Mold filling: Add the drug-containing microneedle solution into the microneedle mold, and use vacuum to allow the drug-containing microneedle solution to fully enter the pinholes of the mold until the mold is filled; Drying and demoulding: The mold containing the microneedle solution is allowed to stand at room temperature and dried, and the pioglitazone hydrochloride hydrogel microneedle patch is obtained after demoulding.

8. The method for preparing a pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes according to claim 7, wherein the blank microneedle solution is stirred at a temperature of 90°C and a speed of 500 r / min for at least 2 hours during the preparation process.

9. The method for preparing a pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes according to claim 7, characterized in that: The preparation process of the electrowetting gel patch includes: Preparation of inner layer electrowetting gel patch: 2.0-5.0% gel skeleton material and 94.5%-98% ultrapure water are weighed respectively by weight, fully stirred and completely dissolved, and then 0%-0.5% conductive material is added to the mixed solution, coated on the first release release film, dried, and then compounded with the second release release film, and cut into inner layer electrowetting gel patches of target size; Preparation of an outer layer electrowetting gel patch: 20-60% moisturizer, 3-12% matrix skeleton material, 0.1-0.5% crosslinker, and 0.02-0.08% complexing agent are weighed respectively by weight and mixed evenly under stirring conditions to obtain a glycerin phase; 15.62-73.68% purified water is taken, 1-5% viscosity enhancer, 2-6% excipient, and 0.2-0.8% crosslinking regulator are added, and fully dissolved to obtain an aqueous phase; the aqueous phase is added to the glycerin phase under stirring conditions until the mixture is evenly mixed to form a gel form, and the gel body is obtained by degassing, and the gel is coated on a first release anti-adhesive film, dried, and then composited with a second release anti-adhesive film; and then cut in two times, first cutting a patch with a diameter slightly larger than that of the inner layer electrowetting gel patch to cover the area of ​​the pioglitazone hydrochloride hydrogel microneedle patch, and secondly cutting out a patch with the same area as the inner layer electrowetting gel from the cut patch to obtain an outer layer electrowetting gel patch with a hollow center; Composite inner layer electrolubricating gel patch and outer layer electrolubricating gel patch: place the inner layer electrolubricating gel patch into the hollow outer layer electrolubricating gel patch, with the inner and outer anti-adhesive films of the patch having the same release force on the same side, then tear off the second release anti-adhesive films of the inner and outer layers of electrolubricating gel, and re-combine with a new second release anti-adhesive film to obtain the electrolubricating gel patch.

10. The method for preparing a pioglitazone hydrochloride microneedle drug delivery system for treating type II diabetes according to claim 7, characterized in that: During the first cutting process of the outer layer electrowetting gel patch: the first cutting diameter of the outer layer electrowetting gel patch is 4 cm larger than the diameter of the inner layer electrowetting gel patch.